Analisis Eksploratif Berita Hoax pada Situs Cek Kebenaran - Puji Winar Cahyo; Ulfi Saidata Aesyi (Teknik Informatika Universitas Pamulang, 2022)
The spread of fake news (hoax) through social media is currently quite difficult for the public to distinguish hoax or actual news. News can be categorized as actual if it comes from a trusted source and is supported by valid source clarification. Therefore, the news that has been spread needs to be clarified to check the truth. Currently, news checking sites are available, including turnbackhoax.id and kominfo.go.id. They have a detail of clarification data on the news classified as hoax or actual. Based on the number of online spreading hoaxes, this study seeks to create a Directory Fact Checker platform, which is a news analysis platform that can display distribution data in graphic form within a certain period of time. Exploratory data analysis was applied to hoax data in 2020. The results of the analysis show that Facebook is the first ranked social media that is often used to spread hoax news, followed by Whatsapp in second place. Meanwhile, judging from the categorization of hoaxes, Content Fabrication is the most widely spread category. Content Fabrication is a news category, 100% of the discussion is fake news. Then in the second rank, followed by the Misleading Content category, Misleading Content is a discussion of news whose contents are twisted with the aim of discrediting.